Response of soil heat-water processes to vegetation cover on the typical permafrost and seasonally frozen soil in the headwaters of the Yangtze and Yellow Rivers - Hu, H. C.; Wang, G. X.; Wang, Y. B.; Liu, G. S.; Li, T. B.; Ren, D. X.; 刘广山 (2009)
The response of soil temperature and moisture to vegetative cover in the active layer of permafrost and seasonally frozen soil were assessed and compared. Soil temperature and moisture, under a range of vegetation covers (92%, 65% and 30%) in the permafrost and vegetation covers (95%, 70%-80%, 40%-50% and 10%) in the seasonally frozen soil, were measured on a daily basis. A decline in vegetation cover led to a decrease in the integral of freezing depth of active permafrost layer, but an increase in seasonally frozen soil. The maximum invasion depth and duration of the negative isotherm during the frozen period and of the positive isotherm during the non-frozen period clearly increased when vegetation cover declined. With a reduction of vegetation cover, the soil moisture in the active layer of the permafrost decreased for depths of 0.20-0.60 m, but increased for depths of 0.60-0.80 m, while for seasonally frozen soil, soil moisture of the entire profile (0.10-1.20 m) increased. Variation in vegetation cover alters soil heat-water processes, but the response to it is different between permafrost and seasonally frozen soil.